2018
DOI: 10.14744/anatoljcardiol.2017.7946
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of selective antegrade cerebral perfusion during prolonged deep hypothermic circulatory arrest: Cerebral metabolism evidence in a pig model

Abstract: Objective:The aim of this study was to elucidate the mechanism of cerebral injury and to evaluate selective antegrade cerebral perfusion (SACP) as a superior neuroprotective strategy for prolonged deep hypothermic circulatory arrest (DHCA).Methods:Twelve pigs (6–8-week old) were randomly assigned to DHCA alone (n=6) and DHCA with SACP (n=6) at 18°C for 80 min groups. Serum S100 was determined using an immunoassay analyzer. The concentrations of cerebral dialysate glucose, lactate, pyruvate, glycerol, and gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Survival rates for neonatal congenital cardiac surgery are currently 90% or higher, but 25%–50% of these patients later developed neurodevelopmental deficits, depending on the complexity of their disease, surgery, and multiple other factors 3,12 . Unfortunately, despite the theoretical advantages of CPB surgery using hypothermia with added cerebral perfusion, recent studies of neurodevelopment outcomes have not shown a significant difference, 13 suggesting that details regarding brain metabolism and causes of neurological injuries during these procedures are not fully understood 14,15 . Improved measurements of brain injury during CPB surgery are likely to enable methods to reduce long‐term negative neurodevelopmental outcomes for these patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Survival rates for neonatal congenital cardiac surgery are currently 90% or higher, but 25%–50% of these patients later developed neurodevelopmental deficits, depending on the complexity of their disease, surgery, and multiple other factors 3,12 . Unfortunately, despite the theoretical advantages of CPB surgery using hypothermia with added cerebral perfusion, recent studies of neurodevelopment outcomes have not shown a significant difference, 13 suggesting that details regarding brain metabolism and causes of neurological injuries during these procedures are not fully understood 14,15 . Improved measurements of brain injury during CPB surgery are likely to enable methods to reduce long‐term negative neurodevelopmental outcomes for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…3,12 Unfortunately, despite the theoretical advantages of CPB surgery using hypothermia with added cerebral perfusion, recent studies of neurodevelopment outcomes have not shown a significant difference, 13 suggesting that details regarding brain metabolism and causes of neurological injuries during these procedures are not fully understood. 14,15 Improved measurements of brain injury during CPB surgery are likely to enable methods to reduce long-term negative neurodevelopmental outcomes for these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation